The Role of Perceived Usefulness, Customer Satisfaction, and Emotional Stability, to Continuance Intention of C2c Online Shop in Surabaya - Danurwindo, Muhammad Al Hakim; Anwar, Muhadjir; Handayani, Wiwik (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2021)
Fenomenon of C2C online shop which is currently in high demand by customers, has effect to the increasing with the amount an level of competition between companies. The purpose of this study is to examine the factors that can influence continuance intention of C2C online shop. The population in this study is consumer of C2C online shop in Surabaya city, and the research sample being C2C online consumers who have bought at least 1 transaction in a minimum period of 1 year purchased by 100 people. The method used in this study is a quantitative method, with PLS (Partial Least Square) analysis technique. The results showed that perceived usefulness and customer satisfaction has effect to the continuance shop intention. Perceived usefulness has effect to the customer satisfaction. Emotional stability has not effect in moderating perceived usefulness into the customer satisfaction. Customer satisfaction has effect tn mediating of the perceived usefulness into the continuance shop intention . The research implications show that continuance shop intention can increase customer purchase transactions at C2C online Shop. Keyword : Continuance shop intention, Customer satisfaction, Perceived usefulness, Emotional stability, C2C Online shop